2007
DOI: 10.1242/dev.02776
|View full text |Cite
|
Sign up to set email alerts
|

New functions for a vertebrate Rho guanine nucleotide exchange factor in ciliated epithelia

Abstract: Human ARHGEF11, a PDZ-domain-containing Rho guanine nucleotide exchange factor (RhoGEF), has been studied primarily in tissue culture, where it exhibits transforming ability, associates with and modulates the actin cytoskeleton, regulates neurite outgrowth, and mediates activation of Rho in response to stimulation by activated Gα12/13 or Plexin B1. The fruit fly homolog, RhoGEF2, interacts with heterotrimeric G protein subunits to activate Rho, associates with microtubules, and is required during gastrulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 62 publications
(64 reference statements)
3
42
0
Order By: Relevance
“…5) that binds to and acts downstream of Mcc. One such candidate is Arhgef11 (also known as PDZ-RhoGEF), a PDZ domaincontaining guanine exchange factor for RhoA whose downstream target is Rho-dependent kinase (ROCK) (Panizzi et al, 2007). Physical association between Mcc and Arhgef11 might provide a platform for ROCK-dependent myosin II activation and remodeling of the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) that binds to and acts downstream of Mcc. One such candidate is Arhgef11 (also known as PDZ-RhoGEF), a PDZ domaincontaining guanine exchange factor for RhoA whose downstream target is Rho-dependent kinase (ROCK) (Panizzi et al, 2007). Physical association between Mcc and Arhgef11 might provide a platform for ROCK-dependent myosin II activation and remodeling of the cytoskeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Support for such a mechanism comes from the colocalization of MCC and myosin II in human mammary epithelial cells (Arnaud et al, 2009). In addition, zebrafish arhgef11 and mcc expression overlap during gastrulation and arhgef11 morphants display a ventral flexure similar to, but an overall phenotype generally less severe than, other Wnt/PCP morphants, probably owing to compensation by the highly related arhgef12 (Panizzi et al, 2007). Thus, it will be interesting to establish formally whether Arhgef11 and Mcc physically interact during zebrafish CE.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, overexpression of dominant-negative forms of Arhgef11 (Arhgef11RGS -the RGS domain of Arhgef11 that competes for Ga 13 binding but contains no functional RhoA-activating DH and PH domains; and Arhgef11DDHPH -which lacks the DH and PH domains) significantly suppressed the epiboly defects resulting from Ga 13 overexpression (Lin et al, 2009). In addition, it has been reported that disrupting RhoGEF or RhoA function causes cardia bifida (Matsui et al, 2005;Panizzi et al, 2007). Thus, we reasoned that Ga 13 may signal through Arhgef11/RhoA to effect S1pr2-triggered myocardial migration.…”
Section: Research Articlementioning
confidence: 92%
“…Capped mRNA was synthesized using the mMessage mMachine Kit (Ambion). The RNAs encoding the following genes were used: gna13a (100 pg) and GNA13 (100 pg) (Lin et al, 2005); the RGS domain of PDZ RhoGEF (arhgef11RGS) (500 pg) or a dominant-negative mutant Arhgef11 lacking the DHPH domain (arhgef11DDHPH) (500 pg) (Panizzi et al, 2007;Lin et al, 2009); s1pr2/mil (200 pg) (Osborne et al, 2008); and sox32 (400 pg) (Stafford et al, 2006). The previously validated morpholino antisense oligonucleotides (MOs) targeting the following genes were used: gna12 (4 ng), gna13a and gna13b (2 ng each) (Lin et al, 2005), and s1pr2/mil (15 ng) (Kawahara et al, 2009).…”
Section: Rna Expression and Morpholinosmentioning
confidence: 99%
“…Basal bodies normally associate apically with a web-like actin network, and experimental treatments that eliminate this network, including mutation in the transcription factor FoxJ1 or prevention of RhoA activation, also prevent basal body docking (16,17).…”
Section: Establishing Xyz Positionmentioning
confidence: 99%